Drug-Coated Balloon Angioplasty for Isolated Medina 0,0,1 Ostial Side-Branch Lesions: Procedural Outcomes, Bailout Stenting, and 12-Month Clinical Follow-Up - Ebru Şahin; Cansu Akdeniz; Begüm Sayın; Hakan Aksoy; Fehmi Kaçmaz; Ali Oto (Medicina, 2026)
Background and Objectives: Stenting isolated Medina 0,0,1 ostial side-branch lesions can result in geographic miss or protrusion into the main vessel. Drug-coated balloon (DCB) angioplasty avoids a permanent implant, but lesion-specific outcome data remain limited. We assessed procedural performance, bailout stenting, and 6- and 12-month outcomes after an intended DCB-only strategy. Materials and Methods: In this retrospective, single-center observational cohort study, we screened 170 patients who underwent coronary DCB treatment at a single center between 1 January 2023 and 31 July 2025. Thirty-one patients with de novo isolated Medina 0,0,1 lesions were included. The primary endpoint was 12-month target lesion failure (TLF), defined as cardiovascular death, target-vessel myocardial infarction, or clinically driven target lesion revascularization (TLR). Results: DCB-only strategy success was achieved in 29/31 patients (93.5%), post-DCB angiographic success in 29/31 (93.5%), and study-defined overall procedural success in 31/31 (100%). Final TIMI grade 3 flow after DCB was present in 30/31 patients; no flow-limiting dissection occurred. Two patients required bailout stenting, one because of deterioration to TIMI grade 2 flow and one because of residual stenosis >30% with recoil. Thirty patients were alive with documented follow-up at 12 months; one patient died from a non-cardiovascular cause at month 1. No TLF was recorded within 12 months. One clinically driven TLR for target-lesion restenosis occurred at month 20, outside the prespecified window. Conclusions: In this selected cohort, an intended DCB-only strategy avoided stent implantation in most patients and had a low bailout rate. The findings support procedural feasibility but do not establish comparative efficacy. Larger prospective studies are required.